PENGARUH ORGANIZATIONAL JOB EMBEDDEDNESS DAN PERCEIVED ORGANIZATIONAL SUPPORT TERHADAP WORK ENGAGEMENT YANG DIMEDIASI OLEH TRUST PADA KARYAWAN PT. PLN (Persero) UNIT INDUK WILAYAH ACEH - Siti Sarah Phonna; Hamdi Harmen (Departemen Manajemen, 2020)
This study aims to measure the effect of Organizational Job Embeddedness and Perceived Organizational Support to Work Engagement with trust as a mediating variable in the PT. PLN (persero) Unit Induk Wilayah employees in Aceh. The sample used in this study was employees of the PT. PLN (persero) Unit Induk Wilayah Aceh, amouting to 115 respondens. Data collection equipment used in this study wa a questionnaire. The sampling technique used is simple probability sampling.HierarchicalLinearModelling(HLM)was used as a method of analysis to determine the effect of all the variables involved.Based on the results of the HLM analysis indicated that Organizational Job Embeddedness positively influence Work Engagement, Perceived Organizational Support positively influence Work Engagement, Organizational Job Embeddedness positively influence Trust, Perceived Organizational Support positively influence Trust, Trust positively inluence Work Engagement, Trust partial mediate the relationship between Organizational Job Embeddedness and Work Engagement, and Trust full mediate the relationship between Perceived Organizational Support and Work Engagement.